OPERATOR SELF ADJOINT PADA RUANG HILBERT - Gunawan Gunawan (Unisda Journal of Mathematics and Computer Science (UJMC), 2015)
In this article, will discuss definition, examples, algebra properties, and somecharacteristic of self-adjoint operators on Hilbert space. In the Hilbert space there are types ofbounded linear operators such as adjoint operators and self-adjoint operators. To investigatecharacteristic of self-adjoint operator required concepts of Hilbert space, operators on Hilbertspaces, Riesz representation theorem, and adjoint operators on Hilbert space. It then takes athought to investigate the characteristic of self-adjoint operators. Discussion of self-adjointoperators more emphasis on understanding the definition, algebra properties, and characteristic ofself-adjoint operators on Hilbert space. The results obtained are algebra properties of self-adjointoperators such as addition, subtraction, scalar multiplication, and multiplication of self-adjointoperators. In addition, some characteristic associated with self-adjoint operators on Hilbert space.